The Effects of Teachers’ Competence on Designing Mindfulness Learning Activity through a Professional Learning Community - Jantakoon, Jakkrit; Thanaphatchottiwat, Suphornthip (International Journal of Psychosocial Rehabilitation, 2024)
The objective of this study was to investigate the effects of teachers’ competence in designing mindfulness learning activities through a professional learning community. The sampling consisted of 24 teachers at the secondary school level who were willing to participate in the study. The research instruments were the plans for designing mindfulness learning activities, the competence evaluation form of learning activity design, self-reflection forms, and learning logs. The study was divided into two loops; the first loop was an initiation, and the second loop was development and capturing lessons learned. The first loop can be divided into 3 steps, which were 1) two days of training, 2) planning mindfulness learning activity design, and 3) observing class and reflection. The second loop consisted of 3 steps that were 1) the revise of mindfulness learning activity design, 2) observe class and reflection, and 3) knowledge management and capture the lesson learned. The statistics for data analysis were mean, standard deviation, and content analysis. The results showed that (1) the competence of teacher on Mindfulness Learning Activity design was rated at a high level (x ̅= 4.35, S.D. = 0.3) 2.) the mindfulness activity that was suitable for secondary school students was moving meditation, also known as Mahasati meditation. Luang Por Teean developed this mindfulness technique. It was highly used for all teachers in the step of set induction; moreover, when teachers notice that their students were distracted at the present moment, mindfulness activities can be applied while the teacher was in the teaching process. Besides meditation practice as normally used, calm classroom activities concepts—breathing, focusing, stretching, and relaxing—or other brain gym activities revealed more useful to apply in the classroom as well. 3) the teacher themselves reflected about the transforming within, such as how they feel different for one thing that they never noticed before, they have more mindfulness, they let their students think without pursuing them to answer. This was a usual way of teaching that now differs from the traditional one. 4) students have readiness for learning, have confidence, are open-minded, and have deep listening skills because of meditation practice applied in classrooms.